Air quality modelling using chemometric techniques - Azid, A.; Rani, N. A. A.; Samsudin, M. S.; Khalit, S. I.; Gasim, M. B.; Kamarudin, M. K. A.; Yunus, Kamaruzzaman; Saudi, A. S. M.; Yusof, K. M. K. K. (University of El Oued, Algeria, 2017)
The datasets of air quality parameters for three years (2012-2014) were applied. HACA gave the result of three different groups of similarity based on the characteristics of air quality parameters. DA shows all seven parameters (CO, O3, PM10, SO2, NOx, NO and NO2) gave the most significant variables after stepwise backward mode. PCA identifies the major source of air pollution is due to combustion of fossil fuels in motor vehicles and industrial activities. The ANN model shows a better prediction compared to the MLR model with R2 values equal to 0.819 and 0.773 respectively. This study presents that the chemometric techniques and modelling become an excellent tool in API assessment, air pollution source identification, apportionment and can be setbacks in designing an API monitoring network for effective air pollution resources management.